Who’s To Blame For Audit Delays: Financial Pressure, Profitability, or The Auditor? - Boli, Hubertus Ade Resha Raditya (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2025)
This research investigates the influence of financial distress, profitability, and audit quality on audit delay among manufacturing firms listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. Audit delay, the time lag between fiscal year-end and audit report issuance, remains a pressing issue in emerging markets, raising concerns over transparency and stakeholder confidence. Using purposive sampling, 100 firm-year observations were analyzed through multiple linear regression. The results reveal that financial distress does not significantly affect audit delay, suggesting that distressed firms may prioritize timely reporting. Contrary to expectations, profitability shows a positive relationship with audit delay, indicating that highly profitable firms may undergo more complex audits due to operational intricacies and enhanced auditor scrutiny. Audit quality, measured by the involvement of Big Four auditors, negatively impacts audit delay, suggesting that high-quality auditors expedite the audit process through greater efficiency and expertise. These findings provide nuanced insights for regulators, investors, and practitioners in managing audit timelines and improving financial reporting practices in Indonesia’s manufacturing sector.